2013
DOI: 10.1200/jco.2012.48.1036
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Trial of Centralized Nurse-Led Telephone-Based Care Coordination to Improve Outcomes After Surgical Resection for Colorectal Cancer: The CONNECT Intervention

Abstract: This trial failed to demonstrate substantial benefit of a centralized system to provide standardized, telephone follow-up for postoperative patients with colorectal cancer. Future interventions could investigate a more tailored approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 18 publications
1
129
0
1
Order By: Relevance
“…Eight trials evaluated educational or supportive care interventions [3542]. Other tested interventions included relaxation (e.g., progressive muscle relaxation [PMR]; n = 2) [43,44], written and verbal emotional expression ( n = 1) [33], an Eastern Body-Mind-Spirit intervention ( n = 1) [45], intimacy enhancement ( n = 1) [34], and a self-efficacy enhancing intervention ( n = 1) [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight trials evaluated educational or supportive care interventions [3542]. Other tested interventions included relaxation (e.g., progressive muscle relaxation [PMR]; n = 2) [43,44], written and verbal emotional expression ( n = 1) [33], an Eastern Body-Mind-Spirit intervention ( n = 1) [45], intimacy enhancement ( n = 1) [34], and a self-efficacy enhancing intervention ( n = 1) [46].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the trials produced null effects of the intervention across all outcome variables [3538,42,44]. These trials tested diverse interventions, including psychoeducation, supportive care, patient navigation, and training in relaxation and other coping skills.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence was inconclusive regarding which patients have the most unmet needs, 10,11 or whether screening for unmet needs may improve patient-reported outcomes. 13,30 The findings of the current study support that telephone-based nursing care is appropriate and acceptable, [10][11][12]15 yet the optimal dose intensity or timing for all patients remain elusive. 31 Although the current intervention did not affect patient-reported outcomes, the entire sample demonstrated patterns of change, which can inform future work.…”
Section: Discussionmentioning
confidence: 66%
“…[10][11][12][13][14][15][16] Outpatient oncology involves a complex system of medical, nursing, and other providers. 15 Prior intervention effects possibly might be enhanced by having patients' own providers deliver visits for managing symptoms, prescribing medications, and titrating doses. Therefore, the current study expanded on prior interventions by testing a model designed to reduce patient-reported symptom burden and to be delivered by each patient's oncology team nurse practitioner (NP).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with findings from previous work. 2 Four cases of symptomatic intra-cerebral recurrence were identified prior to protocol change. Only one of these patients was eligible for radio-surgery.…”
mentioning
confidence: 99%